What Climate Sensitivity Index Is Most Useful for Projections?. Issue 3 (10th February 2018) - Grose, Michael R.; Gregory, Jonathan; Colman, Robert; Andrews, Timothy
Abstract: Transient climate response (TCR), transient response at 140 years (T140), and equilibrium climate sensitivity (ECS) indices are intended as benchmarks for comparing the magnitude of climate response projected by climate models. It is generally assumed that TCR or T140 would explain more variability between models than ECS for temperature change over the 21st century, since this timescale is the realm of transient climate change. Here we find that TCR explains more variability across Coupled Model Intercomparison Project phase 5 than ECS for global temperature change since preindustrial, for 50 or 100 year global trends up to the present, and for projected change under representative concentration pathways in regions of delayed warming such as the Southern Ocean. However, unexpectedly, we find that ECS correlates higher than TCR for projected change from the present in the global mean and in most regions. This higher correlation does not relate to aerosol forcing, and the physical cause requires further investigation. Key Points: We compare transient climate response (TCR), 140 year TCR (T140), and equilibrium climate sensitivity (ECS) as measures of projected warming T140 provides the highest R 2 with the warming relative to preindustrial, but R 2 is higher with ECS in 100 year trends from circa 1960 onward There are large spatial differences in the fit of temperature projections to sensitivity, with lower values in regions of delayed warming